Estudo da carbonização hidrotérmica do resíduo de acerola (malpighia emarginata) com o uso de pré-tratamentos - Costa, Gean Carlos Costa (2022)
The mitigation of environmental impacts from fossil fuels has moved the search for alternative energy sources, where lignocellulosic biomass stands out in the Brazilian scenario due to agribusiness. Among the biomasses resulting from agribusiness is acerola (Malpighia emarginata D.C.), which is commonly consumed after processing, generating a large amount of waste. Hydrothermal carbonization (HTC) emerges as a promising technology in the reuse of these wastes. This process is based on high temperatures and pressure to act in the thermochemical conversion of waste. The main product of hydrothermal carbonization is called hydrochar and presents applications such as solid fuel, adsorbent and soil correction. This work studied the influence of pretreatment in supercritical CO 2 and the use of zinc chloride (ZnCl2) on hydrothermal carbonization of acerola residue. The study was carried out in three stages, the first being the characterization of acerola residue before its application in HTC. The second stage consisted of the realization of HTC obeying the conditions of a fractional factorial planning type central compound, where effects of process variables (temperature, reaction time and additive concentration) on solid yield (RY), superior calorific value (PCS), hydrochar energy efficiency (EY) and oxygenated functional groups (OFG) were evaluated. Solid products (hydrochars) were properly characterized as their physical-chemical properties (proximate analysis), as well as chemical composition (ultimate analysis and FT-IR) also in axial points. The highest RY and EY values were 62.55% and 65.84% (in lower values of temperature, time and concentration). For the variables PCS and OFG, the highest values obtained were 24.46 MJ.kg-1 and 7.03 mmol.g-1 (obtained with the highest values of the independent variables). For immediate analysis, higher temperature and concentration resulted in higher fixed carbon content and consequently influenced the quality of hydrochar by reducing the Ratios O/C and H/C by elemental analysis. An optimization study was also carried out, third stage, aiming at higher RY and EY. Thus, RY and EY values after the optimization study were 59.30% and 60.77%.